2013
DOI: 10.1111/apa.12164
|View full text |Cite
|
Sign up to set email alerts
|

Foetal umbilical artery Doppler in small preterms: (IQ) Neurocognitive outcome at 5 years of age

Abstract: Absent or reversed end-diastolic flow in the umbilical artery (AREDF) was associated with increased risk of SCH in extremely preterm infants (GA <28 weeks).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Eleven studies reported outcomes in association with umbilical artery blood flow. Seven of these did not find an association between abnormal flow in the umbilical artery and neurocognitive outcome (Valcamonico et al, 2004, 2007; Kirsten et al, 2007; Leppänen et al, 2009; Shand et al, 2009; Torrance et al, 2010; Eger et al, 2013). Male fetuses with intrauterine growth restriction and absent or reversed end diastolic flow in the umbilical artery have performed worse on cognitive tests than those with appropriate growth for gestational age (Morsing et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Eleven studies reported outcomes in association with umbilical artery blood flow. Seven of these did not find an association between abnormal flow in the umbilical artery and neurocognitive outcome (Valcamonico et al, 2004, 2007; Kirsten et al, 2007; Leppänen et al, 2009; Shand et al, 2009; Torrance et al, 2010; Eger et al, 2013). Male fetuses with intrauterine growth restriction and absent or reversed end diastolic flow in the umbilical artery have performed worse on cognitive tests than those with appropriate growth for gestational age (Morsing et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…From an obstetric point of view, it is possible to postulate that the widespread use of Doppler sonography and other methods of evaluation of fetal well-being have contributed to define better timing of delivery of VLBW infants. 23,24 Among postnatal improvements, it is possible that better respiratory support, administration of surfactant, reduction of early neonatal sepsis and subsequent nosocomial infections, and improved nutritional support could have contributed to the increase in rates of normal neurodevelopmental outcome at 2 years as recorded in our series. 25,26 In conclusion, this study showed that in a homogenous population from a single institution, the increased survival of VLBW infants was mirrored by increased rates of normal neurodevelopmental outcome at 2 years.…”
Section: Discussionmentioning
confidence: 81%
“…In our analysis, in multivariate models, improved neonatal outcome over time was independent of antenatal steroid administration and mode of delivery, indicating that other factors play a crucial role in this trend. From an obstetric point of view, it is possible to postulate that the widespread use of Doppler sonography and other methods of evaluation of fetal well‐being have contributed to define better timing of delivery of VLBW infants …”
Section: Discussionmentioning
confidence: 99%
“…Among high-risk samples, UA Doppler predicts developmental delay [7][8][9][10] and motor development [9][10][11] at 1-2 years of age, while follow-up studies among 4-9-year-olds reported no association with intelligence quotient (IQ). [12][13][14] Among low-risk pregnancies, high UA-PI was associated with poorer memory functioning among 12-year-olds: differences in general reasoning or academic achievement, albeit in the same direction, were not statistically significant. 15 Evidence from large prospective population-based studies is lacking: while costly, the benefit of these studies is that they are ideally suited for This article is protected by copyright.…”
Section: Introductionmentioning
confidence: 87%